Analisis Kualitas Website Terhadap Kepuasan Penggunaan Elarning Universitas Bina Darma Sebagai Pembelajaran Di Masa Pandemi Covid 19 Menggunakan Metode WEBQUAL 4.0 - Sisca Monita; Ilman Zuhri Yadi (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
E-learning is an electronic distance learning system that uses network and computer technology. There are many models of using e-learning, one of which is the use of e-learning at Bina Darma University during the COVID-19 pandemic, where more use of e-learning and online learning systems during the pandemic period, for this reason the quality of e-learning services can be measured using Webqual. Webqual is a method used to measure website quality based on end users. Webqual is structured in research on 3 dimensions, namely Usability, information, and service interaction. This study aims to determine the quality of the e-learning website of Bina Darma University as student learning taken by 101 students and to find out the most influential indicators in the quality of e-learning. If the alpha value is greater than the R table, then the consistency of the R table is declared valid. On the Likert test scale, it is known that the usability dimension or indicator gets the highest usability level, so the usability dimension has a positive effect on user satisfaction.